Current prevalence, characteristics, and comorbidities of patients with COVID-19 in Indonesia - Dionita Rani Karyono; Anggi Lukman Wicaksana (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Indonesia is currently fighting against a novel coronavirus disease, known as COVID-19. Current information of COVID-19 is crucial for healthcare providers. This study aimed to explore the current prevalence, characteristics, and comorbidities of patients with COVID-19 in Indonesia. We obtained data of the confirmed cases of COVID-19, characteristics and comorbidities from the official website of Indonesia COVID-19 Task Force. The data were extracted, explored and discussed to respond to the research aims. Up to June 3rd, 2020, it was reported there were 28,233 confirmed cases of COVID-19 in Indonesia. The current prevalence of COVID-19 case was 0.11‰ and transmission was distributed to all provinces in Indonesia. Almost one-third of the COVID-19 infections were in the age group of 31-45 years (29.3%) but the highest mortality rate occurred in elderly people (17.68%). Overall, males slightly dominated and contributed only 6.84% to the mortality rate. Cough (76.2%), history of fever (50.4%), and current fever (47.1%) were the most common symptoms among the patients with COVID-19. For comorbidities, patients with COVID-19 had higher numbers of hypertension (52.1%), diabetes (33.6%), and other cardiovascular diseases (20.9%). Those three comorbidities led the greater proportion of deaths among other comorbidities. The COVID-19 pandemic is still a new challenge for Indonesia.